A Concise Synthesis of 25-Hydroxycholesterol from Hyodesoxycholic Acid. (February 2018) - Jin, Can; Wang, Yulei; Sun, Bin; Su, Weike
A simple, efficient and economical method has been developed for the synthesis of 25-hydroxycholesterol in seven steps from hyodesoxycholic acid with an overall yield of 39%. The preparation of the 3β-tetrahydropyranyloxychol-5-en-24-al from 3β-tetrahydropyranyloxychol-5-en-24-oic acid methyl ester with di-isobutylaluminium hydride was achieved instead of using the conventional two-step reaction, thus avoiding the use of the toxic oxidant CrO3 . The terminal product was obtained by hydroxybromination of desmosterol with N -bromosuccinimide/H2 0, followed by reduction and deprotection of the halohydrins with LiAlH4 . This simplified route gave an increased overall yield and used economical and environmentally benign reagents.